The Effectiveness of Islamic Religious Education in the Rehabilitation of Drug Convicts at Women's Penitentiary III Mataram. - Urifah, Dewi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
This research aims to elucidate the effectiveness of Islamic religious education in Women's Penitentiary Institution III Mataram, including its planning, process, as well as the supporting and inhibiting factors in the rehabilitation of drug-related and other inmates. The study employs a quantitative approach involving in-depth interviews with inmates, participatory observation of program implementation, and analysis of relevant documents. Data analysis techniques encompass four stages: data collection, data reduction, data presentation, and conclusion drawing. The application of behaviorist theory in Islamic religious education demonstrates positive outcomes at Women's Penitentiary Institution III Mataram. Inmates receive structured and continuous Islamic religious education. The learning process is supported by prison officers who play an active facilitator role in the learning process. The opportunity for inmates to fully engage in learning activities has successfully transformed their behavioral patterns. Inmates show improvement in their understanding and practice of religion, becoming more disciplined in performing religious rituals such as prayers, reading the Qur'an, and participating in other religious activities. Interviews with inmates also reveal that they feel the program helps them understand the mistakes they have made, and they are committed not to repeat them after their release from prison. Thus, the behaviorist approach in Islamic religious education at Women's Penitentiary Institution III Mataram significantly contributes to the rehabilitation process of drug-related inmates.